Perancangan Sistem Informasi Perencanaan Kebutuhan Bahan Baku Berbasis Teknik Sizing Lot For Lot - Andri Ikhwana; Dudy Mohammad Arifin; Siti Nurisma Ainayah Al Fatihah (Jurnal Algoritma, 2023)
Bagja Printing is a business engaged in manufacturing DTF printing t-shirts. In its company activities, Bagja Printing determines the need for raw materials for production, which is still based on estimates. So that there is often a delay in the production process due to a shortage of raw materials in the middle of the production process. The priority in production is to make a change in planning if there is a shortage of raw materials, because it can cause delays in production activities. Needs planning as part of raw material supply services, which can control the use of raw materials for a product, if too much exceeds the raw material budget will result in bad installments for the company. The aim of this research is to solve problems in planning raw material requirements by designing an information system for planning raw material requirements. The strategy used in business processes is to implement a product production system according to orders (Make to Order) and the lot sizing method (lot for lot) as a plan to meet the needs of raw materials to be ordered from suppliers. The software engineering used is the waterfall method, the stages of which consist of planning, requirements analysis, system design, programming and testing. The result of the creation of this information system is that it makes it easier to monitor raw material needs, obtain inventory information and raw material allocation and obtain accurate information according to reality.